Drug resistance mutations among people living with HIV and ART failure in Bangladesh: a cross-sectional studyResearch in context - Sezanur Rahman; Md Safiullah Sarker; Md Mobarok Hossain; Md Abir Hossain; Mohammad Fakhruddin; Rubel Howlader; Golam Sarwar; Sharful Islam Khan; Mustafizur Rahman (The Lancet Regional Health - Southeast Asia, 2025)
Summary: Background: While maintaining a low HIV prevalence among the general population, Bangladesh is among the few countries in the Asia–Pacific region where the incidence of people living with HIV (PLWH) continues to increase. The National Anti-Retroviral Therapy Program still relies on a ‘Test and Treat’ strategy and faces challenges in treating drug-resistant HIV. This study aims to assess the HIV viral load and drug resistance mutations among key populations (KPs) under anti-retroviral therapy (ART) in Bangladesh. Methods: A total of 110 KPs from 20 drop-in-centers across 11 districts in Bangladesh were enrolled from March 2019 to November 2020 for viral load (VL) testing using Xpert® HIV-1 Viral Load kits. Samples with high VL (≥1000 copies/mL) underwent pol gene sequencing to identify drug resistance mutations. Findings: Most of the participants were men who have sex with men (MSM, 49.1%) followed by men sex workers (MSW, 34.5%), and transgender women (TGW, 13.6%). The median age of the participants was 28 years (IQR: 24–35) and 80% of them were from the capital city, Dhaka. The median time for ART was 11.5 months (IQR: 4.5–29.1), where 15 participants were naïve to ART. Overall, high VL was observed in 23.8%, and virologic failure was in 17.9% among PLWH who were treated for >30 days. HIV-1 subtype C was predominant (43.8%), followed by A1 (25%), CRF01_AE (25%), and CRF02_AG (6.2%). Seven participants showed resistance against Efavirenz, the common drug received from ART centres, and three of them were additionally resistant against Tenofovir Disoproxil Fumarate. Other drugs supplied by ART centres were also found resistant for participants; i.e. 6 against Emtricitabine, 6 against Lamivudine, and 1 against Etravirine. The spatial distribution indicated HIV transmission occurred within and between KPs and drop-in-centers. Additionally, samples that received different ART also clustered together. Interpretation: Evidence suggests that KPs are at a higher risk of virologic failure in Bangladesh, emphasizing the need for routine VL and drug resistance mutation tests as part of the national ART program. This study also advocates for exploring barriers to ART adherence and implementing personalized ART strategies in national ART programs. Funding: The Global Fund.